Quantum physics and mysticism in science teaching - Rocha, Tennile Rany (2020)
Quantum physics emerged in 1900 in an attempt to explain a series of phenomena that classical physics was not capable of. Its consolidation took place in the 1920s as an area of knowledge in an attempt to explain the functioning of things at the level of the dimensions of atoms and subatomic particles. In order to make a counterpoint between the scientific and philosophical-religious viewpoints of mechanics, the interpretations of academic and spiritual bias are emphasized in order to explain to the laity, through an accessible language, the scientific facts and the versions of these facts. As a specific objective, we adopted the analysis and applicability of quantum mechanics in the most diverse contexts throughout history, as well as the misrepresentation of ideas and the use of scientific terms. It is understood that with the results of this research that the attempt to make a link between mechanics and spirituality has no scientific validity. With the study of bibliographic reviews, it is concluded that scientific knowledge is fundamental for the development of critical sense, and consequently for human growth in various aspects and perspectives to know and interpret the world not only in its physical aspects, but also in philosophy, sociology and other fields that proposes a greater reflection. Through the structuring concepts of this area, we can better understand some aspects of what Quantum Physics is about, being an interesting proposal to understand historical evolution of concepts and conceptions that can be found in the most diverse eras, from antiquity to modern times.